(untitled) (Journal of Industrial and Mechanical Engineering, 2023)
An analysis is made of the author’s previous research of real cases of application of the manufacturing characteristics of steel bars for construction used in the country, consulting several companies dedicated to the commercialization of these bars, as well as the users of the same, and it was found that the concepts of "millimeter" and "equivalent" rods, that do not meet specific standards, are used. The current manufacture of rebar built by the process of heat treatment of quenched with surface self-tempered was investigated, verifying technical conformity with the quality of the products. An analysis of the basic properties of the mentioned steels is carried out, providing the necessary information for the understanding of the application of these properties, with the application of specific standards, concluding in the need of knowledge of these properties and regulations by manufacturers and users.